Analisis Penerangan Jalan Umum diatas Jembatan Ampera Kota Palembang - Kms. Andi; Subianto Subianto; Daeny Septi Yansuri (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: This article presents an analysis of public street lighting on the Ampera Bridge, Palembang City, with the aim of evaluating the effectiveness and quality of the existing lighting system. This study aims to identify the strengths and weaknesses of street lighting in this strategic location and provide recommendations for improvement if necessary. Method: used in this study include data collection through field surveys, measuring light intensity using a light meter, and visual observation to assess lighting distribution. The data obtained were analyzed by comparing the measurement results with lighting standards set by local regulations and international guidelines. Results: The study indicate that the lighting system on the Ampera Bridge generally meets the minimum standards required for the safety and comfort of road users. However, there are several areas with inadequate light intensity that can affect visibility at night. Limitations: This study include the limited time of data collection which was only conducted in certain weather conditions, as well as limitations on the measuring instruments used which may affect the accuracy of the results. Contribution: This study is to provide useful insights for authorities and infrastructure designers to improve the quality of lighting on the Ampera Bridge, thereby increasing the safety and comfort of road users. This study also offers recommendations for the development of better and more sustainable lighting systems in the future.